Generation of a Species-Specific Look-Up Table for Fuel Moisture Content Assessment - Yebra, M.; Chuvieco, E. (Selected Topics in Applied Earth Observations and Remote Sensing, IEEE Journal of, 2009)
This study involved the generation of a species-specific Look-Up Table (LUT) for the retrieval of Fuel Moisture Content (FMC) in natural areas dominated by Quercus ilex (Holm oak). Parameter combinations observed in drying Q. ilex samples were used as inputs into the linked PROSPECT and SAILH Radiative Transfer Models (RTM) to avoid unrealistic simulated spectra in the LUT. Terra/MODIS reflectance data, extracted over five plots dominated by Q. ilex, were used to carry out the LUT inversion. This inversion was based on the search for the minimum relative root mean square error (RMSErho*) between observed and simulated reflectance found in the LUT. Different inversion options were tested in order to search for the optimal spectral sampling necessary for accurately estimating FMC. The minimum number of solutions required for the calculation of the estimated FMC was also investigated. The retrieval performance was evaluated with FMC values measured at the five study plots. The most accurate FMC estimation was obtained when using the normalized difference infrared index (NDII6 ) and selecting the ten best cases as the solution (RMSE=26.28%). Finally, a non-oak-specific LUT (generic LUT) was used in the same way to evaluate whether or not the species-specific LUT retrieved FMC more accurately. The results showed that the species-specific LUT provided more accurate FMC estimations than the generic LUT. Only when the number of solutions was higher than 35 was the accuracy of the two LUT similar. Future work will focus on the possibility of generating a LUT adapted to a wider range of species based on data extracted from field measurements and literature.
Keywords: Fuel moisture content (FMC); Holm oak; MODIS; Quercus ilex; Radiative Transfer Models (RTM)

Foliage moisture content estimation from one-dimensional and two-dimensional spectroradiometry for fire danger assessment - De Santis, A.; Vaughan, P.; Chuvieco, E. (Journal of Geophysical Research: Biogeosciences, 2006)
Moisture content in live fuels is a critical variable in fire ignition and fire behavior assessment, but it is very difficult to estimate using traditional methods. Remote sensing measurements provide adequate temporal and spatial coverage to be used operationally in fire danger estimation. Before such applications can be routinely undertaken, reflectance changes caused by water content variations must be clearly separable from other factors in reflectance variation (leaf area index, chlorophyll content, dry matter, observation-illumination angles, etc.). This paper analyzes the effect of these variables in a controlled experiment using young Holm oak (Quercus Ilex) plants, a common Mediterranean species. Spectro-radiometric measurements were performed systematically in laboratory conditions using a GER 2600 spectroradiometer (point measurements, one-dimensional (1-D)) and a Specim hyperspectral camera system (matrix measurements, 2-D). Leaf and canopy biophysical parameters were sampled to control their influence on reflectance as water stress increased. Equivalent water thickness (EWT) and fuel moisture content (FMC) were correlated against several variations of a new index: the Normalized Difference Spectral Index, (NDSI(λ1,λ2)). Results indicate that the choice of suitable spectral bands is critical to control plant physiological effects on reflectance. Strong correlations were obtained between NDSI and both EWT and FMC by applying operational bands at 1108 and 1242 nm (NDSI(1108,1242): r > 0.93), while the shorter near infrared bands (1000 and 860 nm) show a stronger influence of external factors. A combination of 2-D pixel selection techniques and first derivative spectroscopy successfully solved absolute reflectance inconsistencies between 2-D and 1-D measurements, which may prove to be a helpful means of scaling up from leaf to canopy level, and from the ground to airborne observation.
Keywords: fire danger estimation; hyperspectral camera; spectral indices; spectroradiometry